2023
DOI: 10.3390/molecules28073210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Some Bacillus Species from Vegetables and Evaluation of Their Antimicrobial and Antibiotic Potency

Abstract: Numerous natural habitats, such as soil, air, fermented foods, and human stomachs, are home to different Bacillus strains. Some Bacillus strains have a distinctive predominance and are widely recognized among other microbial communities, as a result of their varied habitation and physiologically active metabolites. The present study collected vegetable products (potato, carrot, and tomato) from local markets in Almaty, Kazakhstan. The bacterial isolates were identified using biochemical and phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…Nearly all antibiotics, with the exception of bacitracin, polymyxin, and cloxacillin, were found to be effective against Bacillus species, i.e., Bacillus thuringiensis (BSS25), Bacillus toyonensis (BSS21), Bacillus acidiproducens (BSS16), Bacillus cereus (BSS13), and Bacillus safensis (BSS12) (Table 3). Similar findings on the susceptibility of various antibiotic-susceptible Bacillus species were observed in some recent studies [30,[78][79][80][81]. Here, resistance in specific Bacillus strains to particular antibiotics can result from both inherent (natural) mechanisms and acquired resistance due to the presence of resistance genes associated with the production of resistance enzymes [82].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Nearly all antibiotics, with the exception of bacitracin, polymyxin, and cloxacillin, were found to be effective against Bacillus species, i.e., Bacillus thuringiensis (BSS25), Bacillus toyonensis (BSS21), Bacillus acidiproducens (BSS16), Bacillus cereus (BSS13), and Bacillus safensis (BSS12) (Table 3). Similar findings on the susceptibility of various antibiotic-susceptible Bacillus species were observed in some recent studies [30,[78][79][80][81]. Here, resistance in specific Bacillus strains to particular antibiotics can result from both inherent (natural) mechanisms and acquired resistance due to the presence of resistance genes associated with the production of resistance enzymes [82].…”
Section: Discussionsupporting
confidence: 82%
“…Previously, we found that acetic acid is present in bacterial isolates such as Bacillus subtilis O-3, Bacillus subtilis Md1-42, and Bacillus subtilis Khozestan2 [30]. According to the present study, acetic acid seems to be a common organic compound in almost for all Bacillus species as its presence has been confirmed in the other five Bacillus species, i.e., Bacillus toyonensis, Bacillus acidiproducens, Bacillus cereus, and Bacillus safensis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, Bacillus showed a positive correlation with the accumulation of benzaldehyde, indicating that it may contribute to the almond and cherry flavor of tobacco smoke. On one hand, Bacillus may facilitate the enzymatic conversion of phenylalanine to phenylpyruvic acid, which is further decarboxylated to generate benzaldehyde (Mathatheeranan et al 2023 ); on the other hand, Bacillus has demonstrated its metabolic capacity to produce benzaldehyde, suggesting its involvement as a potential source of benzaldehyde (Koilybayeva et al 2023 ). Moreover, Microbacterium displayed a positive correlation with 3,4-methyl-2,5-furanone, guaiacol, linalool, keto-isophorone, and β-cyclocitral in Sichuan tobacco leaves, these compounds exhibit desirable sensory characteristics, such as floral and fruity aroma, thereby suggesting that Microbacterium may contribute to the floral and fruity fragrance of tobacco.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of this study is to investigate the effectiveness of a biological control agent (BCA) against anthracnose-causing fungus in apples and hot peppers, as well as growth-promoting capability of the PGPR strain. Bacillus species are common bacteria with the potential to produce a wide spectrum of antibiotics ( Koilybayeva et al, 2023 ). These antibiotics can be used to control plant diseases instead of synthetic pesticides and chemical fertilizers.…”
Section: Discussionmentioning
confidence: 99%